Thermal behavior and kinetics assessment of ethanol/gasoline blends during combustion by thermogravimetric analysis - Quiroga, Luis Carlos Rios [UNESP]; Balestieri, Josï¿½ Antonio Perrella [UNESP]; ï¿½vila, Ivonete [UNESP] (Elsevier, 2017)
The use of ethanol as a fuel or as an additive blended with gasoline is very important for most countries, which aim to reduce the heavy dependence on fossil fuels and mitigate greenhouse gases emission. An increased use of ethanol-gasoline blends has placed great relevance on acquiring knowledge about their physical and chemical properties. Thus, knowledge of such properties favors a better understanding of the effect of the percentage of ethanol/gasoline blends on engine performance. Thence, the present study has established a correlation between activation energy and synergetic effects, obtained by a thermal analysis, and ethanol content in gasoline for different blends in order to use this technique as a tool to classify these blends in the process in order to obtain useful energy in spark ignition engines. For such a purpose, a kinetic study has been conducted through a simultaneous thermal analysis system – TGA (thermogravimetry analysis) and DTA (differential thermal analysis) by following the methodology of non-isothermal tests. Thermogravimetric tests were performed and fuel activation energies for gasoline, ethanol, and percentages of 5, 10, 15, 20, 25, 30, 50, and 75% (%v) ethanol mixed with gasoline, which was achieved by the model free kinetics. The analysis results suggest that the theoretical curves characteristics of the thermal decomposition of ethanol-gasoline blends are rather different due to their ethanol content. Furthermore, it was observed significant interactions and synergistic effects, especially regarding those with low ethanol percentage. In conclusion, the thermal analysis techniques can be used as a tool for liquid fuel rating.
Keywords: Ethanol; Free kinetics; Interaction; Synergy; Thermal analysis